Does Marketing Activity Contribute to a Society’s Well-Being? The Role of Economic Efficiency - Sirgy, M. Joseph 1952-; Yu, Grace B.; Lee, Dong Jin; Wei, Shuqin; Huang, Ming-Wei (2012)
Does the level of marketing activity in a country contribute to societal well-being or quality of life? Does economic efficiency also play a positive role in societal well-being? Does economic efficiency also moderate or mediate the marketing activity effect on societal well-being? Marketing activity refers to the pervasiveness of promotion expenditures and number of retail outlets per capita in a country. Economic efficiency refers to the extent to which the economy is unhampered by corruption, burdensome government regulation, and a large informal economy. We used secondary data from the World Bank and other statistical sources to answer these questions. Our study findings suggest that both marketing activity and economic efficiency contribute positively to societal well-being, and that economic efficiency plays more of a mediator than moderator role between marketing activity and societal well-being. The public policy implication of this study is that increases in marketing activity and economic efficiency in countries characterized as low on both dimensions should significantly increase the quality of life in those countries.
Keywords: Marketing systems; Marketing well-being; marketing and quality of life; Economic Efficiency; Marketing activity; Quality of life; Societal well-being